PERSONAL BRANDING ARYA WEDAKARNA PADA FACEBOOK (Analisis Wacana Personal Branding Arya Wedakarna pada periode Juli-Desember 2016) - Meitri Cakraningsih, I Gusti Ayu; Purnawan, Ni Luh Ramaswati; Pradipta, Ade Devia (E-Jurnal Medium, 2017)
Brand is not only used on product and service marketing. Nowadays, brand is developed into personality approach or to be called as “personal branding”. Personal branding is used to make someone looks different than others. others. Many people use this strategy, especially public figures, one of them is Balinese politician Arya Wedakarna. Arya Wedakarna’s personal branding is as “Raja Majapahit Bali’, who saves, protects, and keeps Balinese culture and Balinese people. The aim of this study is to describe how Arya Wedakarna created his personal branding as Raja Majapahit Bali through his social media. This research used qualitative approach and was analyzed by using Teun A Van Dijk discourse. As many as 12 posts on July- December 2016 were analyzed based on eight laws personal branding and three dimension of personal branding. This study found that Arya Wedakarna used eight laws on his post on that period, but not all of eight laws he used in each post. More, Arya Wedakarna has consistency to build his competence and style as Raja Majapahit Bali. Arya Wedakrna also consistent and straight to the rules and values of Majapahit’s culture. Keywords: Personal branding, eight laws of personal branding, three dimension of personal branding, Raja Majapahit Bali.